EXPLORING REGISTER VARIATION IN APPS AKULAKU: A SOCIOLINGUISTICS STUDY - Herlina, Seli; Simatupang, Ervina CM (English Review: Journal of English Education, 2024)
The purpose of the research are (1) to identify the types of registers and (2) to describe the language functions used by the marketing community in Akulaku marketplace apps. This research uses qualitative methods to analyze data and use descriptive methods to explain the data. The object of this research is the written register terms found in Akulaku Marketplace apps. The theories used to classify the data are according to Halliday and Hasan's (1989) theory of register types and Jakobson's (1960) theory of language functions. According to this research, there are 90 data analyzed. The data is categorized into two types of registers, they are closed register 41 data (45,5%) and open register 49 data (54,5%). The functions of the register are referential function 14 data (15,5%), emotive function 20 data (22,2%), conative function 27 data (30%), phatic function 11 data (12,2%), poetic function 11 data or (12.2%) and metalingual function 7 data or (7,7%). This study is expected to increase knowledge of the types of registers and their functions used in marketplace buying and selling activities, while at the same time serving as a valuable resource for reference in education and, in addition, studies in linguistics, mainly in the subject of sociolinguistics.